Frequency, Progression, and Current Management: Report of 16 New Cases of Nonfunctional Pancreatic Neuroendocrine Tumors in Tuberous Sclerosis Complex and Comparison With Previous Reports - Mowrey, Kate; Northrup, Hope; Rougeau, Peyton; Hashmi, S. Shahrukh; Krueger, Darcy A.; Ebrahimi-Fakhari, Daniel; Towbin, Alexander J.; Trout, Andrew T.; Capal, Jamie K.; Franz, David Neal; Rodriguez-Buritica, David (Frontiers in Neurology, 2021)
Background: Tuberous sclerosis complex (TSC) is a genetic condition that causes benign tumors to grow in multiple organ systems. Nonfunctional pancreatic neuroendocrine tumors (PNETs) are a rare clinical feature of TSC with no specific guidelines outlined for clinical management at this time. Our purpose is to calculate the prevalence of nonfunctional PNETs as well as characterize the presentation, current clinical management, and assess the impact of systemic mammalian target of rapamycin (mTOR) on nonfunctional PNETs in TSC. Methods: This retrospective chart review was performed by a query of the TS Alliance’s Natural History Database and the Cincinnati Children’s Hospital TSC Database for patients with nonfunctional PNET. Clinical data from these two groups was summarized for patients identified to have a nonfunctional PNET and compared to previously reported cases with TSC and nonfunctional PNETs. Results: Our calculated prevalence of nonfunctional PNETs is 0.65%. We identified 16 individuals, nine males and seven females, with an average age of 22.0 years (range: 3 - 55 years). The average age at PNET diagnosis was 15.0 years (range: 3 - 46 years). Almost all individuals were diagnosed with a PNET during routine TSC surveillance, 56.3% (n = 9) by MRI, 12.5% (n = 2) by CT, 25% (n = 4) by ultrasound, and 6.2% (n = 1) through a surgical procedure. Nine of the sixteen individuals underwent surgical removal of the PNET. Furthermore, 68.8% (n = 11) had serial imaging following the nonfunctional PNET diagnosis. Eight individuals had a history of using systemic mTOR inhibitors. The rate of growth of the PNETs in individuals not taking mTOR inhibitors was 11 mm/year versus 9 mm/year in individuals taking an mTOR inhibitor. Conclusions: Overall, nonfunctional PNETs occur at younger ages in individuals with TSC and have a higher prevalence in comparison to the general population. The PNETs’ rate of growth was reduced using a systemic mTOR inhibitor.